Progesterone decrease plasma membrane in human sperm with subnormal hypoosmotic swelling test scores - Sisca, Sisca; Yunaini, Luluk; Pujianto, Dwi Ari (Universa Medicina, 2019)
BackgroundProgesterone (P4) is known as a female hormone affecting oocyte maturation and developing uterine wall. A proteomic study identified several receptors including P4 receptors on human sperm. The role of P4 in human sperm cells remains unknown as to whether P4 has non-genomic effects on human sperm. The present study aims to determine the effect of progesterone (P4) on the hyperactivated motility and membrane integrity of human sperm cells.MethodsSemen from normal individuals was obtained from donors. The semen was washed by gradient density centrifugation. P4 was added to each semen sample to final concentrations of 0 (control), 250, 500, 750 and 1000 ng/mL. After the sample treatment was completed, the sperm membrane integrity was assessed with the hypoosmotic swelling test (sodium citrate dihydrate and D-fructose) and the hyperactivated sperm motility parameter was determined with the Computer Assisted Sperm Analyzer [CASA] (Hamilton Thorne, IVOS II, USA). The percentage was then compared between the treatment groups and the control group. The percentage differences were analyzed with the Sigmastat version 2.0 statistical program.ResultsAdministration of P4 increased sperm hyperactivated motility when compared with the control group at a concentration of 500 ng/mL, but the increase was statistically not signicant (p>0.05). In contrast, P4 decreased sperm membrane integrity significantly (p=0.042). And the mean of plasma membrane integrity in all groups was subnormal hypoosmotic swelling test score. ConclusionProgesterone administration tends to increase sperm hyperactivated motility. The integrity of plasma sperm membrane was affected by progesterone.